Impact of premature rupture of membranes and preterm premature rupture of membrane on maternal and neonatal outcomes - Gautham, Kavitha; Thiruvengadam, Nalini; Viswanathan, Ramya; P., Jeeshia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Premature rupture of membrane (PROM) and preterm premature rupture of membrane (PPROM) has significant adverse events in the prenatal, peripartum, and neonatal period. The objective of the present study is to understand the risk factors of PROM and PPROM and delivery outcomes in these subjects along with subgroup analysis on comparison of latent period less than 24 hours (group-1) and more than 24 hours (group-2). Methods: The present data was retrospectively analysed in a private multispeciality birthing centre at Chennai which included a total of 61 cases of PROM and PPROM over a period of six months (January 2022–June 2022). Results: Among 54% (n=33) of the study participants (n=61) were ranging from 30–35 years. Among n=49 PROM cases and n=12 PPROM, n=25 (51%) (including 8 vacuum assisted) and n=6 (50%) mothers had normal vaginal delivery respectively. Also, among study participants, n=13 (21%) subjects were in latent period more than 24 hours and n=49 (80%) subjects were in latent period of less than 24 hours. The maternal complications in both subgroups showed n=1 case of atonic postpartum hemorrhage (PPH) and puerperal pyrexia. Among the neonates, there were 2 incidences of hypoglycemia in both subgroups of LP. Two cases of sepsis in LP <24 hours and in LP >24 hours respectively. Among the 4 neonates with respiratory distress, 3 neonates were shifted to higher centre and were effectively managed. Conclusion: Early diagnosis and prompt management of PROM and PPROM can reduce the risk of maternal and neonatal mortality.